Human Greatness a foundation for sustainable development - Llanos Zuloaga, Llanos Zuloaga (2023)
This essay presents deep reflections on the theme of HUMAN GREATNESS, they are based onreadings of various interdisciplinary as well as an opinion survey of a sample of people with a variety of roles, age groups, education and gender. We have framed the issue from the search for its definitions and links with human developmentand sustainable social development within the framework of the current decade that is aimed at fulfilling the 18 comprehensive objectives of the sustainable development goals for 2030. This theme will have a second article where we will analyze various actors in the possibility of Educating future generations for Human Greatness, an inherent requirement in the search forpeace worldwide.